A model of heat transfer in firefighting protective clothing during compression after radiant heat exposure. (May 2018) - Su, Yun; He, Jiazhen; Li, Jun
This paper presents an experiment-based, multi-medium heat transfer model to study thermal responses of multi-layer protective clothing with an air gap exposed to thermal radiation and hot contact surface. The model considers the dynamical changes of air gap, each layer's fabric thickness, and air content contained in the fabric due to the pressure applied. The fabric heat transfer model developed from this study was incorporated into a human skin burn model in order to predict skin burn injuries. The predicted results from the model were well in agreement with the experimental results. A parametric study was conducted using various contact temperatures and applied pressures and design variables of firefighting protective clothing, such as physical properties of fabric layers and air gap sizes. It was concluded from the parametric study that resistance to transmission of injurious levels of heat decreases as the test temperature and contact pressure increase, and the contact heat transfer can weaken the importance of air gap under radiant heat flux(8.5 kW/m 2 ) for 60 s and compression (pressure: 3 kPa, temperature: 316℃) for 60 s. The findings obtained in this study can be used to engineer fabric systems that provide better protection for contact heat exposure.